New forms of local governance: a theoretical and empirical analysis of the case of Portuguese Municipal Corporations - Tavares, António F. (2005)
This paper is an attempt to identify which factors influence Portuguese local governments to rely on municipal corporations to provide public services. Based on the ideas of the new institutional economics applied to public administration developed by Milgrom and Roberts (1990) and Horn (1995), we argue that influence costs of in-house production and bargaining costs of external delegation to municipal enterprises are the main determinants of the creation of municipal corporations and other types of local public sector organizations external to the local government. An event count model is employed to explain the differences across 278 Portuguese local governments in adopting municipal corporations/enterprises. Results indicate that organizational size, financial dependency, and fiscal stress, as well as ideological concerns and the activity of local interest groups drive the choices of local governance structures.